1966
DOI: 10.1037/h0023120
|View full text |Cite
|
Sign up to set email alerts
|

Information encoding and decision time as variables in human choice behavior.

Abstract: Paired-comparison wagers were offered to Ss under 2 different methods of encoding decision-parameter information. Method 1 provided S with a set of 4 elements of nonindependent parameter information, Method 2 with a subset comprised of 2 independent elements. Ss' choices showed significantly closer correspondence to an EV-maximization decision rule under Method 2, for both independent groups and repeated-measures designs. With repeated measures, it was found that given sufficient decision time, Method 2 transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1968
1968
1991
1991

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Another related finding is that the degree to which a person maximizes EV when choosing among gambles decreases as the number of risk dimensions that need to be processed increases (Herman & Bahrick, 1966). Apparently the greater complexity resulting from the need to integrate a larger number of risk dimensions into a decision leads persons to employ modes of processing that are incompatible with the EV model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another related finding is that the degree to which a person maximizes EV when choosing among gambles decreases as the number of risk dimensions that need to be processed increases (Herman & Bahrick, 1966). Apparently the greater complexity resulting from the need to integrate a larger number of risk dimensions into a decision leads persons to employ modes of processing that are incompatible with the EV model.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the work of Bruner, Goodnow, and Austin (1956) showed that attempts to reduce "cognitive strain" have a very strong influence on information use in decision tasks. Experimental studies demonstrating the influence of informationprocessing considerations in risk taking include the work of Miller and Meyer (1966) on the structure and number of alternatives available to the decision maker; Herman and Bahrick (1966) on the amount of information a person must encode in order to evaluate a bet; and Slovic, Lichtenstein, and Edwards (1965) on the effects of boredom on choices among bets. Concern with the decision maker's information-processing capabilities also underlies Simon's (1957) notion of "satisficing" and Toda's (1962) discussion of the decision processes of a "fungus eater.…”
Section: Oregon Research Institute Eugenementioning
confidence: 99%